Geochemistry of urban waters and their evolution within the urban landscape - Smith, Devin F.; Welch, Susan A.; Rankin, Amelia; Carey, Anne E.; Lyons, W. Berry (Frontiers in Geochemistry, 2024)
Urban populations and the sprawl of urban environments are increasing in the United States as well as globally. The local hydrologic cycle is directly impacted by urban development through greater generation of surface runoff and export of water through subterranean pipes networks to surface water bodies. These pipe networks carry waters that have potentially dramatic effects of the chemistry of groundwater and surface water bodies. In this work, we sampled waters from the Olentangy River and two subterranean outfalls that flow into the river in Columbus, Ohio USA. We measured the major ion, nutrient, and dissolved silica concentrations of each water source to identify how the urban landscape impacts the chemistry of a river that travels from an agricultural landscape to an urban environment. The outfalls had elevated concentrations of all major ions (Na + , K + , Mg 2+ , Ca 2+ , Cl -, SO4 2-) and H4SiO4. However, the Olentangy river typically had greater NO3 -and soluble reactive phosphorous (SRP) concentrations. Sources of elevated ion export include road salts and combined storm runoff (Na + , Cl - ), municipal water treatment practices (K + , Na + , SO4 2-), and concrete pipe weathering (Ca 2+ , Mg 2+ , K + , H4SiO4, SO4 2-). Utilizing stable water isotopes, δ 18 O and δ 2 H, we identified that the water in the pipe networks is typically a mix of multiple precipitation events, but there is evidence of flushing following high-volume precipitation events. The contribution of high TDS waters from subterranean urban outfalls modified the ion abundance in the Olentangy river and produces a tendency towards freshwater salinization syndrome. This is particularly apparent when comparing the chemistry of the urban Olentangy to the agricultural corridor of the river and its other source waters. This research details the transformation of a river as it flows from an agricultural to urban landscape and provides data on the chemistry of source waters that facilitate the river's chemical changes.